Simulation with Arena - Kelton, W. David; Sadowski, Randall P.; Sadowski, Deborah A. (Boston, Mass. : WCB/McGraw-Hill, 1998)
Simulation with Arena provides a comprehensive treatment of simulation using industry-standard Arena software. The text starts by having the reader develop simple high-level models, and then progresses to advanced modeling and analysis. Statistical design and analysis of simulation experiments is integrated with the modeling chapters, reflecting the importance of mathematical modeling of these activities.
1. What is simulation? -- 2. Fundamentals simulation concepts -- 3. A quick peek at arena -- 4. Working with arena -- 5. Modeling basic operations and inputs -- 6. Intermediate modeling and terminating statistical analysis -- 7. Entity transfer and staedy-state statistical analysis -- 8. Detailed modeling -- 9. A sample of further modeling issues and techniques -- 10. Arena customization and integration -- 11. Further statistical issues -- 12. Conducting simulation studies.
includes bibliographical references and index
1
Keywords: Computer simulation